Peculiarities of the course of the wound process in the treatment of acute paraproctitis in patients with type 2 diabetes - Milica, M. M.; Soldusova, V. V.; Postolenko, M. D.; Milica, K. M.; Chobey, S. M. (Modern medical technology, 2023)
Objective. The purpose of the study is to reveal the features of the course of the wound process in patients with acute paraproctitis against the background of diabetes. Methods. An analysis of the results of treatment of acute parаproctitis against the background of diabetes in 328 patients over the past 5 years was carried out. Results. It was found that these patients are define by extensive tissue damage in area and the predominance of gram-negative bacteria in mixed aerobic flora, the addition of anaerobic flora is the cause of the spread of the purulent process and deep destruction of tissues. The synergism of the aerobic-anaerobic flora in combination with the pathogenetic factors of diabetes contribute to a severe and prolonged course of the inflammatory process, as evidenced by the preservation of a high index of intoxication until the 14th day. Conclusions. The criteria for choosing the method of operation are based on the localization of the abscess and the main purulent course, its relationship to the elements of the external anal sphincter, the nature of the scarring process in the area of internal diversion and the function of the closing apparatus of the rectum.